Effect of Drying Time on the Quality of Nori Produced from Kappaphycus alvarezii Seaweed with the Addition of Moringa oleifera Leaves - Mohammad Sayuti; Nur Hidayah; Randi Bokhy Syuliana Salampessy; Siti Zachro Nurbani; Adham Prayudi; Jaulim Sirait; Indra Sakti; Heny Budi Purnamasari; Wa Ode Nurhayatul Fadzilla (Universitas Islam Raden Rahmat, Malang, 2026)
The increasing demand for healthy and practical food products has encouraged the development of nori produced from Kappaphycus alvarezii as an alternative to conventional seaweed sheets. However, drying time is a critical processing factor influencing the sensory, physical, and functional quality of the final product. This study aimed to determine the optimum drying time for producing high-quality nori supplemented with Moringa oleifera leaves. A completely randomized design was applied using three drying times (13, 14, and 15 h), selected based on previous studies indicating that this range provides sufficient moisture removal while minimizing quality deterioration during nori production. The evaluated parameters included sensory characteristics, physical properties, and antioxidant activity. Drying time significantly affected (p < 0.05) all evaluated parameters. The 14 h treatment produced the highest sensory acceptance, with appearance (8.02), texture (8.24), taste (8.48), aroma (8.40), and color (8.36), closely resembling commercial nori. This treatment also provided balanced physical properties (thickness 0.23 mm and tensile strength 12.18 N) and moderate antioxidant activity (IC₅₀ = 137.27 ppm), which was superior to that of commercial nori (199.25 ppm). These findings demonstrate that drying for 14 h is the optimum condition for producing high-quality nori from Kappaphycus alvarezii and provides a practical processing reference for seaweed-processing industries and small-scale nori manufacturers utilizing locally available raw materials.